Exploring the biosorption of nickel and lead by Fusarium sp. biomass: kinetic, isotherm, and thermodynamic assessment - Moreira, Daniele [UNESP]; Alves, Gabriela Souza; Rodrigues, João Marcos Madeira [UNESP]; Estevam, Bianca Ramos; Sales, Douglas Henrique [UNESP]; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Vasconcelos, Ana Flora Dalberto [UNESP]; Boina, Rosane Freire [UNESP] (Springer Nature, 2024)
Fungal biomass is as a cost-effective and sustainable biosorbent utilized in both active and inactive forms. This study investigated the efficacy of inactivated and dried biomass of Fusarium sp. in adsorbing Ni2+ and Pb2+ from aqueous solutions. The strain underwent sequential cultivation and was recovered by filtration. Then, the biomass was dried in an oven at 80 ± 2 °C and sieved using a 0.1-cm mesh. The biosorbent was thoroughly characterized, including BET surface area analysis, morphology examination (SEM), chemical composition (XRF and FT-IR), thermal behavior (TGA), and surface charge determination (pH-PZC and zeta potential). The biosorption mechanism was elucidated by fitting equilibrium models of kinetics, isotherm, and thermodynamic to the data. The biosorbent exhibited a neutral charge, a rough surface, a relatively modest surface area, appropriate functional groups for adsorption, and thermal stability above 200 °C. Optimal biosorption was achieved at 25 ± 2 °C, using 0.05 g of adsorbent per 50 mL of metallic ion solution at initial concentrations ranging from 0.5 to 2.0 mg L−1 and at pH 4.5 for Pb2+ and Ni2+. Biosorption equilibrium was achieved after 240 min for Ni2+ and 1440 min for Pb2+. The process was spontaneous, mainly through chemisorption, in monolayer for Ni2+ and multilayer for Pb2+, with efficiencies of over 85% for both metallic ion removal. These findings underscore the potential of inactive and dry Fusarium sp. biomass (IDFB) as a promising material for the biosorption of Ni2+ and Pb2+. Graphical Abstract: (Figure presented.)
Keywords: Adsorption; Biomass; Filamentous fungi; Industrial wastewater; Metal removal; Metallic ion; Ni(II); Pb(II)